Money demand, financial liberalization and currency substitution in Malaysia - Wong, Jing Lee (Universiti Malaysia Sarawak (UNIMAS), 2010)
(:hiS study attempts to examine the relationship between money demand and real gross domestic product (GDP), interest rate, real effective exchange rate and the fmancial liberalization indicator in Malaysia. The ADF unit root test and 10hansen-luselius co integration test were utilized to analyze the annual time series data which range from 1978 to 2007. Then, vector error correlation estimate was used to investigate the impact of money demand to the variabley Growth in real GDP level encourages the increase in the demand for Ml, which is consistent with most of the findings of empirical studies I done on money demand. Also, the result showed a positive relationship of real effective exchange rate demand for money. In other words, currency substitution effect existed in the money demand function. Nevertheless, the interest rate indicates negative impact on narrow money demand. The fluctuation in the short-run interest rate encourages money holder to switch to holding other financial assets, which is a better option to gain return on the money. As for financial liberalization, the relationship between narrow money demand is negative because the financial innovations had change the demand for Ml to broad money. A stable long-run equilibrium relationship exists among the money demand function and variables.